2019
DOI: 10.1021/acs.jpcc.8b10460
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiller-Induced Ionic Conductivity Enhancement and Relaxation Property Analysis of the Blend Polymer Electrolyte Using Non-Debye Electric Field Relaxation Function

Abstract: The enhancement of conductivity of a composite polymer as a dielectric material is an essential requirement for electrostatic storage devices. We have modified the microstructure of the polymer matrix by introducing an insulating nanofiller SiO2. The effect of such a filler on the ionic conductivity of the composite polymer electrolyte has been investigated using a variety of experimental techniques along with the non-Debye type of relaxation functions. We have achieved optimum conductivity enhancement at a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Moreover, Arya and Sharma [83] reported ion mobility ( μ ) in the range 10 −10 to 10 −12 cm 2 V −1 s −1 . More recently, Patla et al [84] have also documented ion mobility ( μ ) in the range 1.8 × 10 −4 to 9.5 × 10 −11 cm 2 V −1 s −1 for polyvinylidene fluoride (PVDF) based polymer nano-composites incorporated with ammonium iodide (NH 4 I) salt. From the results of the present work, it is clear that ion transport parameters can be easily estimated from the Trukhan model.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Arya and Sharma [83] reported ion mobility ( μ ) in the range 10 −10 to 10 −12 cm 2 V −1 s −1 . More recently, Patla et al [84] have also documented ion mobility ( μ ) in the range 1.8 × 10 −4 to 9.5 × 10 −11 cm 2 V −1 s −1 for polyvinylidene fluoride (PVDF) based polymer nano-composites incorporated with ammonium iodide (NH 4 I) salt. From the results of the present work, it is clear that ion transport parameters can be easily estimated from the Trukhan model.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Arya and Sharma [83], documented the ion mobility (μ) in the range 10 −10 to 10 −12 cm 2 V −1 s −1 . Recently, Patla et al [91] reported the ion mobility (μ) in the range 1.8 × 10 −4 to 9.5 × 10 −11 cm 2 V −1 s −1 for PVDF based polymer nano-composites incorporated with ammonium iodide (NH 4 I) salt.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity profile of the FTIR spectra was taken after background correction under an air atmosphere. The characteristics of the FTIR band were analysed using previous literature [25,26]. The peak shifting, generation of new peaks, and peak broadening confirmed the microstructural variation of polymer composites.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…Most of the research work was carried out on the lithium (Li) and sodium (Na) salt due to its lower cation size and high transport number [16,23]. The ionic conductivity was enhanced by different methods like polymer blending, plasticizer addition, and nanofiller incorporation [18,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%